2018
DOI: 10.1155/2018/4179421
|View full text |Cite
|
Sign up to set email alerts
|

Effect of TIPA on Chloride Immobilization in Cement‐Fly Ash Paste

Abstract: Utilization of sea sands and coral aggregate for concrete in ocean construction is increasingly attracting the attention all over the world. However, the potential risk of steel corrosion resulting from chloride in these raw materials was one of the most concerned problems. To take this risk into account, chloride transporting to the surface of steel should be hindered. e formation of Friedel's salt in hydration process is widely accepted as an effective manner for this hindrance. In this study, an attempt to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…e hydration products were characterized with 29 Si MAS NMR. It was reported that six peaks were found in NMR spectrum of hydrated cement-FA paste [12,38,39]; Q 1 and Q 2 represented the chain-end Si-O tetrahedrons and middle-chain Si-O tetrahedrons in hydration products; Q 2 (1Al) denoted the middle-chain groups where one of the adjacent tetrahedral sites was occupied by Al 4+ ; Q 0 , Q 3 , and Q 4 represented the Si-O tetrahedrons in unhydrated cement minerals and Si-O tetrahedrons in FA, respectively. A Bruker Advance III400 spectrometer was adopted to carry out 29 Si-NMR (solid-state nuclear magnetic resonance), operating at 79.5 MHz, with rotation frequency of 5 kHz and the delay time of 10 s. Tetramethylsilane was used as 29 Si standard.…”
Section: Nmrmentioning
confidence: 99%
See 2 more Smart Citations
“…e hydration products were characterized with 29 Si MAS NMR. It was reported that six peaks were found in NMR spectrum of hydrated cement-FA paste [12,38,39]; Q 1 and Q 2 represented the chain-end Si-O tetrahedrons and middle-chain Si-O tetrahedrons in hydration products; Q 2 (1Al) denoted the middle-chain groups where one of the adjacent tetrahedral sites was occupied by Al 4+ ; Q 0 , Q 3 , and Q 4 represented the Si-O tetrahedrons in unhydrated cement minerals and Si-O tetrahedrons in FA, respectively. A Bruker Advance III400 spectrometer was adopted to carry out 29 Si-NMR (solid-state nuclear magnetic resonance), operating at 79.5 MHz, with rotation frequency of 5 kHz and the delay time of 10 s. Tetramethylsilane was used as 29 Si standard.…”
Section: Nmrmentioning
confidence: 99%
“…where C is a constant; P i and V i stand for the mercury pressure and intruded pore volume at step i; and D stands for the fractal dimension of the pore surface [45][46][47][48]. erefore, equation 9is expressed as equation (12). e fractal dimension of the pore surface can be obtained by the slope of the curve log (V 1/3 n /r n ) versus log (W n /r 2 n ).…”
Section: Nmrmentioning
confidence: 99%
See 1 more Smart Citation
“…Cement particles have surface charges which causes them to flocculate when in contact with water while the addition of chemical admixtures into the fresh concrete mix releases the trapped bound water within the gel matrix [22,23]. However, other research reports that the effect of these chemical admixtures is to increase the amount of bound chloride when chloride diffusion into hardened concrete occurs from external sources [30,31]. This is due to the greater surface area of the hydration products produced by the flocculation of cement particles and release of bound water caused by the admixtures [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…One was to promote the formation of FS or KS to chemically bind chloride ions; the second was to hasten the hydration to produce more amount of C-S-H gel to physically adsorb the chloride ions; the last was to improve the pore structure to hinder the migration of chloride ions. For example, one reason for supplementary cementitious materials (SCM), such fly ash (FA) and ground granulated blast furnace slag (GGBS), to promote the binding capacity was that the dissolution of aluminates could be facilitated in the process of pozzolanic reaction, which could expedite the formation of FS or KS, thereby promoting chemical binding [ 12 , 13 ]. The other reason was that pore structure and the hydration degree were also improved, which promoted the migration resistance and physical binding.…”
Section: Introductionmentioning
confidence: 99%